Concentración de Hg, Pb, Cd, Cr y As en hígado de Carcharhinus limbatus (Carcharhiniformes: Carcharhinidae) capturado en Veracruz, México - Fernando Mendoza-Díaz; Arturo Serrano; Liliana Cuervo-López; Alejandra López-Jiménez; José A. Galindo; Agustín Basañez-Muñoz (Revista de Biología Tropical, 2013)
La contaminación de los ecosistemas marinos y costeros por metales pesados en el Golfo de México es uno de los problemas que afectan a los recursos naturales del medio acuático. Los tiburones por situarse en niveles tróficos superiores de la red alimenticia acumulan y magnifican cantidades considerables de contaminantes. Por esta razón, el objetivo de este trabajo fue determinar la concentración de cuatro metales pesados (Hg, Cd, Pb y Cr) y un metaloide (As) en el tiburón punta negra (Carcharhinus limbatus) por medio de espectrofotometría de absorción atómica con flama y generador de hidruros. Se muestrearon 19 hígados de tiburones capturados cerca de Tamiahua, Veracruz entre noviembre 2007 y marzo 2008, de los cuales 12 fueron machos adultos, una hembra adulta, tres machos jóvenes y tres hembras jóvenes. Las concentraciones máximas registradas para cada metal fueron: Hg=0.69mg/ kg, Cd=0.43mg/kg, As=27.37mg/kg, Cr=0.35mg/kg. El Pb no fue detectado, no al menos la cantidad mínima de detección requerida por el espectrofotómetro de absorción atómica (0.1mg/kg). Ninguna de las muestras analizadas rebasó los límites máximos permisibles por las leyes mexicanas y americanas. Concentration of Hg, Pb, Cd, Cr and As in liver Carcharhinus limbatus (Carcharhiniformes: Carcharhinidae) captured in Veracruz, Mexico. Pollution by heavy metals in marine ecosystems in the Gulf of Mexico is one of the hardest conservation issues to solve. Sharks as top predators are bioindicators of the marine ecosystem health, since they tend to bioaccumulate and biomagnify contaminants; they also represent a food source for local consumption. Thus, the objective of this study was to study the possible presence of heavy metals and a metalloid in livers of Carcharhinus limbatus. For this, a total of 19 shark livers were taken from animals captured nearby Tamihua, Veracruz, Mexico from December 2007 to April 2008. 12 out of the 19 captured sharks were males, one was an adult female, three were juvenile males, and three juvenile females. Four heavy metals (Hg, Pb, Cd, and Cr) and one metaloid (As) were analyzed in shark livers using an atomic absorption spectrophotometry with flame and hydride generator. Our results showed that the maximum concentrations found were: Hg=0.69mg/kg, Cd=0.43mg/kg, As=27.37mg/kg, Cr=0.70mg/kg. The minimum concentrations found were: As=14.91mg/kg, Cr=0.35mg/kg. The Pb could not be determined because the samples did not have the spectrophotometer minimum detectable amount (0.1mg/kg). None of the 19 samples analyzed showed above the permissible limits established by Mexican and American laws. There was a correlation between shark size and Cr and As concentration (Pearson test). The concentration of Cr and As was observed to be higher in bigger animals. There was not a significant difference in heavy metals concentration between juveniles and adults; however, there was a difference between males and females. A higher Cr concentration was found in females when compared to males. None of the samples exceed the maximum limit established by the laws of Mexico and the United States of America. Much longer studies are needed with C. limbatus and other species caught in the region, in order to determine the degree of contaminants exposure in aquatic ecosystems and to identify potential health risks to consumers.